My Lady Mage - Morgan, Alexis (Sigent Eclipse fantasy/romance, 2012)
When she calls upon a band of enchanted warriors to save her people from dark magic, Merewen finds a champion and lover in their leader, Gideon, but when their enemies fight back with unexpected might, she faces losing everything.